The clinical utility of musculoskeletal ultrasonography in hemiplegic shoulder rehabilitation poststroke - Liu, Jun; Pan, Huijuan; Bao, Yong; Huang, Li; Hu, Yunyun (Frontiers in Rehabilitation Sciences, 2025)
ObjectiveThis study aimed to assess the utility of musculoskeletal ultrasound (MSUS) in the rehabilitation of stroke patients with hemiplegic shoulder pain.MethodsWe conducted a study involving 80 stroke patients with hemiplegia and concomitant shoulder pain on the affected side, admitted to our hospital between April 2020 and March 2021. MSUS was used to evaluate shoulder structures, including the long head of the biceps brachii tendon (BICT) and its sheath, rotator cuff, subacromial–subdeltoid (SA–SD) bursa, labrum, acromioclavicular ligament, acromiocoracoid ligament, and acromion–greater tuberosity (AGT) distance. We compared pre- and post-rehabilitation measurements of supraspinatus tendon (SST) thickness, BICT sheath effusion thickness, SA–SD bursa effusion thickness, AGT distance, and visual analog scale (VAS) scores. Statistical significance was set at P < 0.05.ResultsPost-rehabilitation, the SST thickness on the hemiplegic side showed a statistically significant reduction (P = 0.023). No significant difference was observed in the mean maximum rupture diameter (P = 0.796). Both BICT sheath effusion (P < 0.001) and SA–SD bursa effusion (P < 0.001) exhibited significant decreases. The AGT distance on the hemiplegic side also demonstrated a statistically significant change (P < 0.001). Additionally, the VAS score significantly improved post-rehabilitation (P < 0.001).ConclusionMSUS is a feasible and reproducible tool for monitoring rehabilitation progress in stroke patients with hemiplegic shoulder pain.